Profil Persiapan Guru Dalam Mengajarkan Numerasi Berdasarkan Pengalaman Mengajar - Maulana, Abdillah Putra; Lestari, Nurcholif Diah Sri; Kurniati, Dian; Pambudi, Didik Sugeng (Kadikma, 2024)
The purpose of this study is to find out the preparation made by teachers in teaching numeracy. The type of research used was qualitative which was carried out at SDN Jember Lor 1. The research subjects were 2 people who had met the criteria of teaching experience. The data collection technique uses interviews. The instrument used has been validated by 2 expert lecturers. Test the validity of the data using reference materials. The collected data was analyzed descriptively and qualitatively supported by interview recordings and photographs. The results of this study concluded that there was a difference in the preparation for teaching numeracy with the description: 1) teachers with low teaching experience were more creative in compiling teaching modules, 2) teachers with high teaching experience better understood the model and assessment of numeracy learning.